2016
DOI: 10.1080/00016489.2016.1260156
|View full text |Cite
|
Sign up to set email alerts
|

Identification of KCNQ1 compound heterozygous mutations in three Chinese families with Jervell and Lange-Nielsen Syndrome

Abstract: Compound mutations of KCNQ1 were found to be the genetic etiology of four patients from three families. Among the six KCNQ1 mutations, c.546C > A was identified as a novel mutation, c.965C > T had been reported in JLNS, while c.683 + 5G > A, c.1484_1485delCT, c.905C > T and c.1831G > A were previously reported in LQT1. In addition to congenital profound hearing loss in all subjects, two sibling subjects showed typical JLNS cardiac phenotype of prolonged QTc and recurrent syncopal episodes. One subject presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In general, a dominant-negative inhibitory effect is suspected for dominantly inherited missense Kv7 variants that retain the C-terminal tetramerization region. For example, for Kv7.4 missense variants, a dominant-negative inhibitory effect has been demonstrated for p.L47P, p.N264S, p.S269F, p.S273A, p.L274H, p.W276S, p.T278A, p.L281M, p.L281S, p.G285C, p.G285S, p.L295P, p.G296S, p.G321S, and p.R433W [ 52 , 54 , 58 , 68 , 73 , 74 , 76 ]. However, these studies would not rule out the possibility that some missense variants are also cytotoxic.…”
Section: Remaining Questions and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, a dominant-negative inhibitory effect is suspected for dominantly inherited missense Kv7 variants that retain the C-terminal tetramerization region. For example, for Kv7.4 missense variants, a dominant-negative inhibitory effect has been demonstrated for p.L47P, p.N264S, p.S269F, p.S273A, p.L274H, p.W276S, p.T278A, p.L281M, p.L281S, p.G285C, p.G285S, p.L295P, p.G296S, p.G321S, and p.R433W [ 52 , 54 , 58 , 68 , 73 , 74 , 76 ]. However, these studies would not rule out the possibility that some missense variants are also cytotoxic.…”
Section: Remaining Questions and Future Directionsmentioning
confidence: 99%
“…Not a Kv7.4 variant, but the expression of a missense Kv7.2 variant, Kv7.2 M518V , was reported to induce neuronal death [ 123 ]. Missense mutations that were reported to impair cell membrane targeting of Kv7.4, i.e., p.L274H, p.W276S, p.L281S, p.G285C, p.G285S, p.G296S, and p.G321S [ 58 , 68 , 81 ], are of particular interest because impaired cell membrane targeting implies a structural defect in a mutated protein, an intracellular accumulation of which could induce cellular stress. It should be pointed out that many previous studies reporting a dominant-negative inhibitory effect for Kv7 variants used transiently transfected cells.…”
Section: Remaining Questions and Future Directionsmentioning
confidence: 99%
“…Prior to MPS, screening on common variants in GJB2 , SLC26A4, or MT‐RNR1 was conducted and no causative variants were detected in the three participants. Massively parallel sequencing covering 110 NSHL associated genes was then completed in the subjects using Agilent SureSelect Target Enrichment Kit (Agilent Technologies, Santa Clara, CA) and Illumina HiSeq 2000 System (Illumina, San Diego, CA) as described (Wang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…These reports do not provide unequivocal conclusions about the association of the variant with arrhythmic disorders. In addition, co-occurrence with another pathogenic variant has been reported ( KCNQ1 c.1484_1485delCT, p.L496AfsX19, [ 41 ]), providing supporting evidence for a benign role.…”
Section: Cases Presentationmentioning
confidence: 97%
“…An in vitro splice assay showed that this variant causes exon 4 skipping and premature protein truncation [ 32 ]. This variant was reported in the literature in individuals affected with LQTS and Jervell and Lange-Nielsen syndrome [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. These reports do not provide unequivocal conclusions about the association of the variant with arrhythmic disorders.…”
Section: Cases Presentationmentioning
confidence: 99%